THE EFFECT OF VITICULTURAL AND CHEMICAL PRACTICES ON ASSESSMENT OF POST HARVEST SHELF LIFE AND UNIFORM COLOUR DEVELOPMENT IN GRAPE CVS. RED GLOBE AND CRIMSON SEEDLESS - PORIKA, H. K.; J. , SATISHA; P. SAMPATH KUMAR; K. K. UPRETI (The Bioscan, 2018)
It is a prerequisite that export grapes should have more shelf life to remain fresh for longer period and evenly coloured to fetch high price in the International market. Considering this, a trial was conducted in clusters collected from 4 years old vines of Red Globe and Crimson Seedless during 2015-16 and 2016-17. The obtained results revealed that, the minimum PLW was recorded in Red Globe (13.58 and 11.86%) and Crimson Seedless (23.56 and 15.53%), respectively in both seasons, the minimum percentage of fallen berries in Red Globe (2.52 and 1.01%), respectively in season-I and II whereas, in Crimson Seedless it reflected in season II (1.93%) by the application of berry thinning, ethrel dip (500 ppm) and basal leaf removal. The maximum total anthocyanins in Red Globe (2.80 and 4.54 mg/g FW), in Crimson Seedless (3.19 and 3.47 mg/g FW) was registered with similar treatment as stated above. The assessment for colour characteristics by colorimetric readings (L*, C, H and CRIG value) also reflected in similar application of treatment. Hence, the results stated that clusters treated with good viticultural practices along with ethrel dip resulted in maintaining the even colour development, quality and post harvest shelf life at ambient room temperature.